Dual Band Electrodes in Generator-Collector Mode: Simultaneous Measurement of Two Species - Barnes, E; Lewis, G; Dale, S; Marken, F; Compton, R (Elsevier, 2013)
A computational model for the simulation of a double band collector-generator experiment is applied to the situation where two electrochemical reactions occur concurrently. It is shown that chronoamperometric measurements can be used to take advantage of differences in diffusion coefficients to measure the concentrations of both electroactive species simultaneously, by measuring the time at which the collection efficiency reaches a specific value. The separation of the electrodes is shown to not affect the sensitivity of the method (in terms of percentage changes in the measured time to reach the specified collection efficiency), but wider gaps can provide a greater range of (larger) absolute values of this characteristic time. It is also shown that measuring the time taken to reach smaller collection efficiencies can allow for the detection of smaller amounts of whichever species diffuses faster. The case of a system containing both ascorbic acid and opamine in water is used to exemplify the method, and it is shown that mole fractions of ascorbic acid between 0.055 and 0.96 can, in principle, be accurately measured.